Clinicopathological characteristics, prognosis, and the significance of FNA-CT in sporadic medullary thyroid microcarcinoma: a 10-year retrospective study - Wang, Mingjun; Chen, Wenjie; Li, Peiheng; Gong, Yanping (Frontiers in Endocrinology, 2025)
ObjectiveThe detection rate of sporadic medullary thyroid microcarcinoma (micro-sMTC) has increased with advancements in diagnostic techniques. In this study, we aimed to investigate the clinical characteristics, optimal management, prognosis, and the significance of calcitonin assays in fine-needle aspiration washout fluid (FNA-CT) for micro-sMTC, which remain unclear.MethodsThis retrospective study included 73 patients with micro-sMTC who underwent initial surgery between November 2014 and November 2024 at the Division of Thyroid Surgery, Department of General Surgery, West China Hospital, Sichuan University. Clinicopathological features, factors associated with lymph node metastasis (LNM), dynamic risk stratification, and progression-free survival (PFS) were analyzed. Additionally, the significance of FNA-CT was investigated in relation to early diagnosis, surgical decision-making, and prognosis in these patients.ResultsThe mean age of the patients was 48.3 years, with a female predominance (60.3%). Following the introduction of FNA-CT in 2020, the detection rate of micro-sMTC increased. Most patients (91.8%) presented with asymptomatic suspicious thyroid nodules detected on ultrasonograms. The median tumor size and basal calcitonin level were 7.0 mm and 68.0 pg/mL, respectively. FNAC accurately identified MTC in only 20 (24.4%) of 82 nodules from the 73 patients. Hemithyroidectomy was performed in 13 (17.8%) patients, including 4 with contralateral nodules. After a median follow-up of 34.0 months (range: 6.0–124.0 months), 58 (79.5%) patients achieved an excellent response, while 12 (16.4%) and 3 (4.1%) patients exhibited biochemical incomplete and structural incomplete responses, respectively. LNM was significantly associated with suspicious lymph nodes on ultrasonograms, multifocality, and high-grade tumors. High-grade histology and advanced clinical stage were associated with an unfavorable response to initial surgery and independently predicted poor PFS (both p < 0.05). Patients in the FNA-CT group had lower basal calcitonin and carcinoembryonic antigen (CEA) levels, smaller tumors, less advanced staging, and fewer high-grade tumors (all p < 0.05) than those in the non-FNA-CT group. However, early diagnosis via FNA-CT was not associated with improved PFS.ConclusionsDespite its typically favorable prognosis, micro-sMTC may exhibit certain aggressive features. High tumor grade and advanced clinical stage are independent prognostic factors of poor PFS and may guide postoperative surveillance strategies. FNA-CT shows potential value in facilitating earlier diagnosis of micro-sMTC and identifying suitable candidates for hemithyroidectomy.